Designing User Interface on “HewanKu” Application Using User Centered Design Method - Devi Fedrianingsih; Evlyn Jane Putri; Meilani Jesica; Irfan Tigranaufal Nugraha; Danke Hidayat; Ramma Dwi Rachmat; Mahatmadi Ariq Mayangkara; Ade Riyanti; Afifah Rodhiyatun Nisa (Batrisya Education, 2025)
This research aims to design the user interface of the HewanKu application using the User Centered Design (UCD) method, in order to improve user experience in buying and selling livestock transactions. UCD is applied to ensure that the design of the application interface is in accordance with user needs and preferences. The research method involves the stages of user needs analysis, design, prototype testing, and design iteration based on user feedback. Application testing was conducted using a Black Box Testing approach to ensure that the application functions according to specifications without navigation errors or feature failures. The results showed that the application of UCD succeeded in producing a more intuitive and efficient interface, as well as increasing user trust and satisfaction in transactions. The conclusion of this research is that the combination of UCD and Black Box Testing is effective in creating an application that is easier to use and reliable to support livestock buying and selling transactions. Keywords: Black Box Testing, Livestock Transactions, Mobile App, User Centered Design, User Interface